1970
DOI: 10.3126/kumj.v7i1.1766
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tuberculosis in enlarged neck nodes, our experience

Abstract: Objectives: To determine the incidence of tuberculous lymphadenitis in enlarged neck nodes. Materials and methods: Continuous prospective study is carried out in the department of otorhinolaryngology head & neck surgery, Kathmandu Medical College, Kathmandu, during two years, from January 2006 to January 2008. The study included a group of 155 patients with cervical lymphadenopathy. Each patient underwent a detail clinical Ear, Nose and Throat (ENT) examination and a battery of investigations which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
37
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 11 publications
12
37
0
3
Order By: Relevance
“…Studies from Saudi Arabia and Nepal had their average age of patients with cervical lymphadenopathy between 36 and 39 years which was similar to ours [15,16]. in our study malignant etiology group have their peak incidences between 55 and 65 years.…”
Section: Agesupporting
confidence: 88%
See 1 more Smart Citation
“…Studies from Saudi Arabia and Nepal had their average age of patients with cervical lymphadenopathy between 36 and 39 years which was similar to ours [15,16]. in our study malignant etiology group have their peak incidences between 55 and 65 years.…”
Section: Agesupporting
confidence: 88%
“…In a recent study done in Saudi Arabia by Tawfiq et al showed reactive lymph nodes to be commonest (52 %) followed by malignancy (32 %) followed by granulomatous disease (15.5 %) [15]. Studies done in Nepal showed the commonest cause for cervical node was TB, followed by reactive lymphadenitis and then malignancy [16]. In a study done in Mexico TB was seen in 48 % of individuals having cervical lymphadenopathy [18].…”
Section: Size and Associated Symptomsmentioning
confidence: 98%
“…Submandibular lymph node group involved in 33.91%. [10][11][12][13] In the present study, Neck swelling was present in all cases (100%). Fever was the second most common symptom in 60%, followed by loss of weight in 46.96 %, malaise in 36.52%, loss of appetite in 23.48%, cough in 18.26%, difficulty in swallowing in 6.96%, and change in voice was present in 6.96% respectively.…”
Section: Discussionmentioning
confidence: 58%
“…Other causes were unknown primary in 1.74% and non-Hodgkin's lymphoma in 0.87% of cases. 3,7,8,12,15,16 Age distribution according to aetiology showed that nonmalignant cervical lymphadenopathy was common in age less than 40 years, while malignant cervical lymphadenopathy was common after 40 years of age. This difference was not significant statistically.…”
Section: Discussionmentioning
confidence: 99%
“…The broad spectrum of etiology of neck masses that ranged from congenital benign to acquired neoplastic lesions is varied and related to multiple factors. [3][4][5] The demographic characteristics of children presented with neck masses varied with the location and residency of patients. 5,6 Clinical and radiographic evidences are enough to establish accurate diagnoses in pediatric neck masses except in cases of nonspecific clinical conditions as in inflammatory lymphadenopathy or malignancies in which open biopsy is required.…”
Section: Introductionmentioning
confidence: 99%